USING GAME MAKING MACROMEDIA FLASH MX ACTIONSCRIPT ON PROFESSIONAL - Sahra Wulandari; Linda Wahyu Widianti, Skom, MMSI Linda Wahyu Widianti, Skom, MMSI (Jurnal Sistem Informasi, 2006)
aking games using Action Script language is the main emphasis on the writing ofthis scientific creativity with simple tools, but are interactive and interesting. Thegame created with Macromedia Flash MX application illustrates the battle betweenthe robot and its enemies outside the space, which is equipped with interesting voicesand an evaluation or scoring that makes the game more challenging.One of the interesting information about the games created with this flash is flexiblein the queue can be played on a computer network or the Internet.So that can be used as an additional facility on the webpage.Scientific writing is to explain the process of making games ranging from the designstage of components, script creation and publication of a flash file with the facilitiesalready available in Flash MX application.